2021
DOI: 10.3390/pathogens10010057
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 6A Induces Dendritic Cell Death and HMGB1 Release without Virus Replication

Abstract: Human herpesvirus 6A (HHV-6A) is a common virus that has important immunomodulatory effects. Dendritic cells (DC) are key players in innate and adaptive immunity and are implicated in the pathogenesis of many human diseases, including infections. (1) Background: Previous studies have demonstrated suppressive effects of HHV-6A on key DC functions. (2) Methods: human monocyte derived dendritic cells were inoculated with HHV-6A and viral replication, cell viability, and release of high mobility group box 1 (HMGB1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…[ 27 ] The HMGB1 release was driven by the human herpesvirus 6A. [ 28 ] Importantly, the HMGB1 level was elevated in the serum of EV71‐induced HFMD patients and was aggravated in severe and critical HFMD patients. [ 12 ] Consistent with our previous study, the present study also found that the HMGB1 expression was increased in the serum of HFMD patients and EV71‐infected RD cells in a time‐ and MOI‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 ] The HMGB1 release was driven by the human herpesvirus 6A. [ 28 ] Importantly, the HMGB1 level was elevated in the serum of EV71‐induced HFMD patients and was aggravated in severe and critical HFMD patients. [ 12 ] Consistent with our previous study, the present study also found that the HMGB1 expression was increased in the serum of HFMD patients and EV71‐infected RD cells in a time‐ and MOI‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…HHV-6 induces syncytia but also gives semi-lytic infection with dying cells and cell debris. DC exposure to HHV-6A result in cell death and release of high mobility group box 1 (HMGB1) protein ( 80 ). This may occur also in the CNS as HHV-6A can induce vigorous apoptosis of a human oligodendrocytes ( 81 ).…”
Section: Hhv-6 In Msmentioning
confidence: 99%
“…HHV-6A infection of DCs can cause DC cell death [ 145 ]. High mobility group box 1 (HMGB-1) is a protein located in the nucleus that acts as an alarmin and is capable of stimulating the innate immune system through either active release or passive release following cell death [ 146 ].…”
Section: Immune Cell Responsesmentioning
confidence: 99%
“…In addition, infection altered the cytokine profile. While TH1 cytokine expression was unaffected, levels of cytokines produced by TH2 cells were significantly elevated relative to the control [ 145 ].…”
Section: Immune Cell Responsesmentioning
confidence: 99%